Applying DBA Research Concepts in attending any UAE based SME Challenges Post Covid 19 and Global Market Slowdown - Salloum, Hussein (International Journal of Scientific Research and Management (IJSRM), 2021)
This report discusses how a DBA degree would enable investigate evolving types of leadership styles that Small and Medium Enterprises, particularly in manufacturing sector in United Arab Emirates develop since the outbreak of Covid-19 pandemic on multiple levels of strategies, financial, human resource, as well as health and safety. The study considers the management research concepts and methodologies in one case of one Dubai based SME firms amid year 2020 pandemic challenges. It draws a roadmap for the research process, and formulates the plan to conduct purposeful and demanding topic from an ethical and business perspective that would have similar effects on similar SMEs in the region.